FIGURATIVE LANGUAGE IN THE TOBA BATAK SAUR MATUA CEREMONY - Marlina Tampubolon; Sumarsih Sumarsih; Busmin Gurning (Universitas Negeri Medan, 2018)
The aims of this study are to describe the kinds of figure of speech and discover the existence of figure of speech that is delivered by Hula-hula, boru, and dongan tubu in Toba Batak saur matua ceremony. This research was conducted by using qualitative descriptive. The data were the utterances gathered from umpasa that are delivered by Hula-hula, boru, and dongan tubu of 3 Toba Batak saur matua ceremonies in Rantau prapat and Tarutung. The data analyzed by using theory of descriptive analysis. from identifying the data that are needed for this research, classifying the data based on the theory of figures of speech and analyzing the data based on the theories that were used. The findings are there were 7 out of 10 kinds of figure of speech were found in the umpasa of Toba Batak saur matua ceremony. The most dominant figure of speech in Toba Batak saur matua ceremony was simile. Toba Batak people tent to deliver umpasa through simile which compared between two dissimilar things by using the comparative term (like, as) and described to the first qualities of the second of invest the first with connotations inherent in the other. Keyword: Figurative Language, Toba Batak, Saur matua ceremony